Source language text, parallel text and model translated text: a pilot study in teaching translation (2007)
The advance in cultural-oriented perspectives in Translation Studies has sometimes played down the text linguistic nature of translation. A pilot study in teaching translation was carried out to make students aware of the text linguistic character of translating and help them to improve their translation skills, particularly with an emphasis on self-awareness and self-correcting strategies. The theoretical background is provided by the Dynamic Translation Model (2004, 2005) proposed by the author, with relevant and important contributions taken from Genette's (1982) transtextuality phenomena (hypertext, hypotext, metatext, paratext, intertext) and House and Kasper's (1981) pragmatic modality markers (downgraders, upgraders). The key conceptual role of equivalence as a defining feature of translation is also dealt with. The textual relationship between Source Language Text (SLT) is deemed to be pivotal for performing translation and correction tasks in the classroom. Finally, results of the pilot study are discussed and some conclusions are drawn.